Barrierefrei. - Kurtz, Andrea (LPV Media, 2013)
Oft ist es nur eine Stufe, die den Zugang erschwert. Der verein Sozialhelden schafft Abhilfe.
Keywords: Handel; Einzelhandel; Laden; Rampe; Behinderter; Selbsthilfe; Ladenlokal; Geschäftsraum; Zugänglichkeit; Barrierefreiheit; Rollstuhl; Bürgerschaftliches Engagement